A scoping review of knowledge syntheses in the field of evaluation across four decades of practice. (April 2020) - Lawarée, Justin; Jacob, Steve; Ouimet, Mathieu
Abstract: This scoping review of 62 knowledge syntheses published in evaluation-focused journals between 1979 and May 2018 provides a portrait of synthesis practices and their evolution in the mainstream of the field of evaluation. Concerns surrounding the production of knowledge syntheses to answer policy questions are not new in the field of evaluation. However, during this last decade, knowledge synthesis methods have expanded as a means to go beyond the limits and constraints of singular evaluations. This scoping review reveals and discusses two key issues with regards to the expansion of knowledge synthesis practices within the field of evaluation: the diversity—and muddling— of methodological practices and synthesis designs, and the frequent omission of quality appraisals.